Prescrição de Anti-Inflamatórios Não Esteroides a Doentes com Diabetes Mellitus em Portugal - Vieira, M (2019)
INTRODUCTION: Portugal presents the highest incidence of stage 5 chronic kidney disease in Europe. It is speculated that a high consumption of non-steroidal anti-inflammatory drugs (NSAIDS) may contribute to this high incidence. Our aim was to characterize the prescription of non-steroidal anti-inflammatory drugs to patients with diabetes mellitus in Portugal. MATERIAL AND METHODS: We analyzed the national prescription database in triennium 2015 - 2017. In patients with diabetes mellitus, we evaluated the prescription of non-steroidal anti-inflammatory drugs according to age, gender and region of the patient and specialty of the prescribing physician. We evaluated the prescription of non-steroidal anti-inflammatory drugs in all patients with diabetes mellitus, in patients with presumed renal impairment, and in those with concomitant prescription of angiotensin converting enzyme inhibitors or angiotensin receptor antagonists. RESULTS: We analyzed 23 320 620 prescriptions, corresponding to 610 157 adults, including 104 306 patients with diabetes mellitus. The most prescribed non-steroidal anti-inflammatory drugs were ibuprofen (20.1%), metamizole (14.7%), and diclofenac (11.4%). The prescription of non-steroidal anti-inflammatory drugs was higher in females, in patients aged 51 - 70 years and in the Alentejo region. Non-steroidal anti-inflammatory drugs were prescribed to 70.6% of patients with diabetes mellitus, from which 10.6% were prescribed ≥ 10 packages during the three years. Among patients with diabetes mellitus on angiotensin converting enzyme inhibitors/angiotensin receptor antagonists and with presumed reduction in kidney function, 69.3% were prescribed non-steroidal anti-inflammatory drugs and 11.5% were prescribed ≥ 10 packages during the three years. DISCUSSION: The level of prescribing of non-steroidal anti-inflammatory drugs to patients with diabetes mellitus is high. The concern of reducing non-steroidal anti-inflammatory drugs prescription to patients already on angiotensin converting enzyme inhibitors/angiotensin receptor antagonists and/or decreased renal function does not seem to exist. CONCLUSION: In Portugal, the level of prescribing of non-steroidal anti-inflammatory drugs to patients with diabetes mellitus should be reduced, particularly in the subgroups identified with higher prescription and with higher risk of progression to stage 5 chronic kidney disease.